Encouraging the production of narrative responses to past-behaviour interview questions: effects of probing and information - Brosy, Julie; Bangerter, Adrian; Ribeiro, Sandrine (My University, 2020)
In behavioural interviews, past-behaviour questions invite applicants to tell a story about a past job-related situation. Nevertheless, applicants often do not produce stories on demand, resorting to less appropriate responses. In a sample of real selection interviews (Study 1), only 50% of applicants’ responses to past-behaviour questions were indeed stories. We explored two factors that may increase applicants’ storytelling tendencies: probing and information about past-behaviour questions. In two experiments simulating selection interviews, we manipulated recruiter probing during the interview (Study 2) and the level of participants’ information about the expected answer format of past-behaviour questions (Studies 2 and 3). Probing induced participants to tell more stories and to include more narrative diversity in their stories, but there was no effect of giving participants information or not. More information did help participants to tell less pseudostories (generic descriptions of situations). Analyses of participants’ thoughts and emotions experienced during question-answering suggest that finding an appropriate example to narrate is a major problem. Storytelling rate also varied by competency. Findings are relevant for theories of behaviour elicitation in selection situations.
Keywords: Selection interview; past-behaviour question; storytelling; probing; behaviour elicitation